2018
DOI: 10.1557/mrs.2018.72
|View full text |Cite
|
Sign up to set email alerts
|

Multicaloric materials and effects

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
64
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 93 publications
(68 citation statements)
references
References 43 publications
0
64
0
4
Order By: Relevance
“…[141] In recent times, multicaloric materials that can support more than one type of caloric effect have been investigated. [21,29,59,78,[142][143][144][145] Multicaloric phenomena can be envisioned as the superposition of the primary colors of light as shown schematically in Figure 3. The three primary caloric effects, namely, MC, EC, and mC correspond to the three primary colors of light as blue, green, and red, respectively.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
See 1 more Smart Citation
“…[141] In recent times, multicaloric materials that can support more than one type of caloric effect have been investigated. [21,29,59,78,[142][143][144][145] Multicaloric phenomena can be envisioned as the superposition of the primary colors of light as shown schematically in Figure 3. The three primary caloric effects, namely, MC, EC, and mC correspond to the three primary colors of light as blue, green, and red, respectively.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…Multicaloric effects may be observed in multiferroic oxides that can simultaneously exhibit more than one ferroic order parameter such as ferroelectricity, ferromagnetism, or ferroelasticity. [21,29,78,[142][143][144] Since 2012, several groups have theoretically predicted multicaloric effects in various ferroic materials. [145][146][147][148][149] Models depicting the design and optimization of solid-state coolers based on multicaloric oxides have shown that temperature differences as high as 25 K can be created using multilayered structures.…”
Section: Wwwadvmatinterfacesdementioning
confidence: 99%
“…Though electrocaloric cooling has probably the lowest technology readiness level among the three, it promises the most direct conversion of electrical to thermal energy. The last article by Stern-Taulats et al 14 addresses new cooling concepts, such as coupling ferroic-caloric effects to trigger multicaloric effects.…”
Section: In This Issuementioning
confidence: 99%
“…An extended introduction in ferroic cooling as well as to the particular magnetocaloric materials and devices, electrocaloric, elastocaloric and multicaloric effects can be found in another recent special issue. The present issue goes even more into depth and addresses all aspects, which range from the fundamentals towards application.…”
Section: Figurementioning
confidence: 99%
“…Forf erroic cooling, first-and second-order phase transitions are both relevant.F irst-orderp hase transitions can result in huge entropy changes,b ut these materials are only suitable in an arrow temperature range around the transition temperature.I na ddition, the associated hysteresisl osses reduce the cooling efficiency.S econd-order phase transitions exhibit no hysteresis,b ut commonly only reach al ower entropy change,w hicha dvantageously can be used within a broader temperature range.T he dispute between first-and second-order phase transitions in ferroic cooling is covered in depth within ar ecent Special Issue on hysteresis. [3] An extended introductioni nf erroic cooling [4] as well as to the particular magnetocaloric materials [5] and devices, [6] electrocaloric, [7] elastocaloric [8,9] and multicaloric effects [10] can be found in another recents pecial issue.T he present issue goes even more into depth and addresses all aspects,w hich range from the fundamentals towards application. It answers most of the questionsa sked at the beginning of the interdisciplinary priorityp rogram FerroicCooling (SPP 1599).…”
mentioning
confidence: 99%